Molecular switching in nanospaces - Dube, Henry; Durola, Fabien; Ajami, Dariush; Rebek, Julius (Journal of the Chinese Chemical Society, 2010)
Switching devices that operate on the molecular level lie at the heart of nanomachinery. The energies involved range from scores of kcal/mol during cleavage or formation of covalent bonds to a few kcal/mol when the signals are changes in conformation. Here we examine three systems that use light, metal/ligand binding, and acid/base chemistry as switching devices to transfer molecules in and out of the confined environments of encapsulation complexes or cavitands. The events are reversible and the original states can be recovered by treatment with brief heating, conventional chelating agents, or changes in protonation states, respectively. The control over these spaces augurs well for applications in drug delivery and sensors for small molecules.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Azobenzene; Cavitand; Photoisomerism; Reversible encapsulation; Signaling